Biosynthesis in vitro of Caenorhabditis elegans phosphorylcholine oligosaccharides - Cipollo, John F. (National Academy of Sciences, 2004)
The biosynthesis in vitro of phosphorylcholine oligosaccharides in Caenorhabditis elegans has been investigated. Here we show that extracts of C. elegans' microsomes transfer phosphorylcholine from L-α-dipalmitoyl phosphatidylcholine to hybrid and complex type N-linked oligosaccharides containing mannose residues disubstituted with N-acetylglucosamine. The reaction products are consistent with structures reported for C. elegans as well those found in the filarial nematodes Acanthocheilonema viteae, Onchocerca volvulus, and Brugia malayi, strongly supporting the concept that the phosphorylcholine oligosaccharide biosynthetic enzymes are conserved in this group of organisms. Because it is thought that phosphorylcholine substitution of oligosaccharides modulates host immune response in filarial infections, this in vitro system may help in gaining an understanding of the basis for this response.